Cockpit Compatibility Evaluation RB-57F and F-4D Aircraft - Hockwalt, John R. (1972)
The results of a compatibility study performed on the RB-57F and the F-4D aircraft are presented in this report. Compatibility of crew members with the above aircraft, while wearing an A/P22S-6 flying outfit and other ancillary equipment, was determined. A 2-1/2 inch thick arctic survival overcoat cushion was found to place the large to extra large crew member above the B-57F aircraft design eye point. A second mockup cushion (with maximum thickness reduced to 1 inch) was found to be satisfactory. The PCU-15/P torso harness was found to restrict the forward movement of the small to extra small crew member in the RB- 57B cockpit. The A/P22S-6 flying outfit was found to be compatible for use in the F-4D aircraft.